Molecular characterization and functional analysis of cytochrome P450 genes in the yellow fever mosquito Aedes aegypti (Diptera: Culicidae) - Issa, Moustapha Soumaila (Kansas State University, 2014)
Cytochrome P450 monooxygenases (P450s) are important enzymes involved in the metabolism of a variety of xenobiotics, including insecticides and plant allelochemicals, and endogenous compounds, including juvenile hormones, ecdysteroids and fatty acids, in insects. Despite rapid advances in revealing various P450 genes in insects, our knowledge on the role of these genes in detoxification of insecticides is very limited. This research was to perform a genome-wide analysis of P450 genes and evaluate the role of selected P450 genes in detoxification of three commonly used pyrethroid insecticides in the yellow fever mosquito (Aedes aegypti). Our genome-wide analysis of revealed 159 P450 genes that can be classified into 18 families and 63 subfamilies. These genes are distributed in four clans, including 11 genes in the CYP2 clan, 80 in the CYP3 clan, 58 in the CYP4 clan and 10 in the mitochondrial CYP clan. The largest families are CYP6, CYP9, CYP4 and CYP325. The intron-exon organization of the genes is very diverse among the gene families, and the highest conservation of gene structures was observed in the CYP6 and CYP9 families predominantly containing single-intron genes. The phylogenetic analysis suggested that the CYP6 and CYP9 families might be derived from a common ancestor. The expression patterns of five transcripts including three individual genes (CYP6AA5, CYP6AL1 and CYP9J32) and two alternative splicing variants (CYP4J16A and CYP4J16B) of CYP4J16 were investigated in various tissues and at different developmental stages of the mosquito. Our results indicated differential expressions of these transcripts in different tissues and at different developmental stages examined. Furthermore, the exposure of the mosquitoes (larvae and adults) to each of three pyrethroid insecticides (permethrin, cypermethrin and deltamethrin) resulted in either down or up-regulation of these transcripts. Functional analyses of the selected P450 transcripts were conducted by using RNA interference (RNAi) followed by insecticide bioassay. RNAi was achieved by feeding mosquito larvae with chitosan/double stranded RNA (dsRNA) nanoparticles or injecting dsRNA to the adults. For the larvae, we obtained relatively low repressions of the P450 transcripts but the repressions were sufficient for carrying out our functional studies. Our study showed increased mortalities by 41.2% to cypermethrin when CYP6AA5 was silenced and 46.0% to permethrin when CYP9J32 was silenced. Similarly, the injection of dsRNAs in adults resulted in significant repressions of the P450 transcripts, and subsequent insecticide exposures led to a 29.3% increase in the adult mortality to cypermethrin when CYP6AA5 was silenced. Our further analysis of the nuclear receptor HR96 in the up-regulation of the P450 genes showed that when HR96 was silenced by RNAi, the up-regulation of CYP4J16B by cypermethrin was reduced by 10.1-fold but silencing HR96 did not affect the up-regulation of other P450 genes examined. These results suggest that HR96 is likely involved in regulating the expression of CYP4J16B in Ae. aegypti. However, different regulatory mechanism (s) may be involved in the up-regulation of other P450 genes examined. Model structure of CYP6AA5 was created by homology modeling and insecticides substrates were docked into the active site of this protein. Our results indicate that all three insecticides can fit into the catalytic pocket. The interaction distances between the heme iron and the putative aromatic hydroxylation site were 9.2, 9.4 and 7.2 Å for permethrin, cypermethrin and deltamethrin, respectively, whereas for aliphatic hydroxylation site these distances were 5.3, 2.8 and 2.9 Å. These results showed that CYP6AA5 may be able to metabolize cypermethrin and deltamethrin preferentially by aliphatic hydroxylation as indicated by the close interaction with the heme iron.
Keywords: Cytochrome P450; Aedes aegypti; RNA interference; Detoxification; Pyrethroids; Entomology (0353); Molecular Biology (0307); Toxicology (0383)